Effect of non‐Saccharomyces yeasts on the volatile chemical profile of Shiraz wine. (3rd February 2017) - Whitener, M.E. B.; Stanstrup, J.; Carlin, S.; Divol, B.; Du Toit, M.; Vrhovsek, U.
Abstract: Background and Aims: This study evaluated the impact that the non‐ Saccharomyces yeasts, Torulaspora delbrueckii (TD), Lachancea thermotolerans (LT), Pichia kluyveri (PK), Metschnikowia pulcherrima (MP), Candida zemplinina (CZ) and Kazachstania aerobia (KA), in sequential inoculation with Saccharomyces cerevisiae (SC), had on the volatile chemical profile of Shiraz wine. Methods and Results: Shiraz grape must was inoculated with monocultures of the non‐ Saccharomyces yeasts, which were allowed to ferment until 2% v /v ethanol concentration was reached at which point, SC was added to complete the alcoholic fermentation. The control was SC in monoculture. The final wines were subjected to solid phase microextraction‐GC × GC‐time of flight‐MS to evaluate the untargeted volatile metabolite profile of each treatment. Each fermentation produced a unique chemical profile. The LT–SC sequential fermentation was the most significantly different from the control primarily in the ester, alcohol and terpene profile. The KA–SC sequential fermentation had the highest amount of volatile acidity, and the PK–SC sequential fermentation had a relatively high amount of acetaldehyde and a few esters. The MP–SC sequential fermentation also revealed a higher concentration of several esters. The TD–SC sequential fermentation was notable for its lack of a distinct pattern in comparison with that of the other fermentations. Conclusions: Given these characteristics, the LT–SC sequential fermentation showed the most potential for increased chemical complexity of the Shiraz volatile profile. Significance of the Study: The results demonstrate that there is no clear, singular trend for how different, non‐ Saccharomyces species of yeast – once thought to be wholly unfavourable in wine fermentations – will impact wine chemistry, flavour or quality. Each species presents unique metabolic characteristics, many of which could be beneficial, and their potential application in the wine industry should be considered.